PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN BIOLOGI MATERI VIRUS PADA SISWA FASE E DI SMA - Suci Yunita Sari; Rayendra; Nofri Hendri; Mutiara Felicita Amsal (STKIP Subang, 2025)
This study focuses on the development of an Augmented Reality (AR)–based learning media for teaching the topic of viruses in Biology for students in Phase E at SMA Negeri 1 Bonjol. The problem underlying this research is the difficulty faced by students in understanding the abstract and complex concept of viruses, the use of conventional teaching media that lack interactivity, and the low level of student motivation. The purpose of this research is to develop AR media that is valid, practical, and effective in improving students’ understanding and motivation in learning the virus material. The research was conducted using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The product developed is an Android application named ViRex (Virus Real Experience), supported by a student worksheet (LKPD) and teacher guide. ViRex includes realistic 3D virus models, interactive AR features and offline usability. Data collection instruments included expert validation sheets, student practicality questionnaires, and pre-test and post-test for effectiveness analysis. The results of expert validation showed that the product is categorized as highly valid in both material and media aspects. The practicality test with students indicated that the application is easy to use, attractive, and engaging. Effectiveness analysis through pre-test and post-test showed a significant improvement in students’ learning outcomes and motivation. In conclusion, the AR-based learning media developed in this study is feasible, practical, and effective to be used as an innovative learning tool for teaching virus concepts in Biology for senior high school students.